A multi-technique nondestructive approach for characterizing the state of conservation of ancient bookbindings; Journal of Thermal Analysis and Calorimetry; Vol. 132, iss. 2 - Sfarra S. Stefano; Regi M. Mauro; Tortora M. Mariagrazia; Casieri C. Cinzia; Perilli S. Stefano; Paoletti D. Domenica (2018, 2018)
Title screen